Preoperative imaging biomarkers combined with tap test for predicting shunt surgery outcome in idiopathic normal pressure hydrocephalus: a multicenter retrospective study - Gao, Wei; Liu, Wei; Ying, Yuqi; Zeng, Qingze; Wang, Jiadong; Lin, Jingquan; Guo, Xinxia; Jiang, Hongjie; Zheng, Zhe; Zhu, Zhoule; Zhu, Junming (Frontiers in Aging Neuroscience, 2025)
ObjectivesThe study aims to investigate the predictive performance of preoperative imaging features combined with tap test for the outcomes of ventriculoperitoneal (VP) shunt in idiopathic normal pressure hydrocephalus (iNPH).MethodsIn this multicenter retrospective study, 166 iNPH patients who underwent VP shunt surgery between August 2019 and November 2023 were included. Preoperative clinical characteristics and imaging features were collected. Preoperative clinical assessment and at least 3 months of postoperative follow-up were performed. Multivariable logistic regression, sensitivity, specificity, and the area under the receiver operating characteristic curve (AUC) were used to evaluate predictive performance.ResultsOut of 166 total patients, 96 were responders and 70 non-responders. The tap test showed significant difference between two group (p < 0.01). Multivariable logistic regression identified that a positive disproportionately enlarged subarachnoid space (DESH) sign (OR = 0.09, 95% CI: 0.04–0.22, p < 0.001) and a sharper callosal angle (CA) (OR = 0.97, 95% CI: 0.95–1.00, p = 0.02) were associated with symptom improvement after shunt. The sensitivity, specificity, and AUC of tap test were 0.64, 0.60, and 0.62, respectively. Combining CA and the tap test increased sensitivity to 0.85, while combining DESH, CA, and the tap test improved specificity and AUC to 0.67 and 0.72, respectively.ConclusionThe findings suggest that the imaging features DESH and CA, when combined with the tap test, enhance the prediction of VP shunt outcomes in iNPH patients. Despite the improved predictive capability, further research focusing on innovative biomarkers for VP shunt is warranted.